THU0122 Safety of surgery in patients with rheumatoid arthritis treated by rituximab in routine care: Data from the french air registry. (23rd January 2014) - Godot, S.; Gottenberg, J.E.; Paternotte, S.; Pane, I.; Combe, B.; Sibilia, J.; Flipo, R.-M.; Schaeverbeke, T.; Ravaud, P.; Toussirot, E.; Berenbaum, F.; Mariette, X.; et al.
Abstract : Background: The risk of post-surgical complications related to the use of non anti-TNF biological agents in patients with rheumatoid arthritis (RA) remains unclear. The aim of this study was to investigate the safety of surgery in RA patients treated by rituximab (RTX) in routine care using data from the AutoImmunity and Rituximab (AIR) registry. Methods: The AIR registry has been set up by the French Society of Rheumatology and includes RA patients treated with RTX. The charts of patients undergoing any surgery during the year following an infusion of RTX were reviewed in order to i)describe the frequency of postsurgical complications, ii) to compare the characteristics of patients w/o complications and iii) to identify the parameters associated with postoperative side effects in a multivariate logistic regression analysis. Results: 1972 patients have been enrolled patients until August 2010. 133 patients underwent surgery during the year after an infusion of RTX for a total of 140 procedures including 94 orthopaedic surgeries (67%). Twelve complications (8.5% of procedures) occured in 9 patients (6.7%): 6 deep infections and 2 scars or superficial infections at the surgical site, 1 pulmonary infection, 1 delayed healing, 1 deep venous thrombosis and 1 death related to a septic shock. Infections at surgical site were reported for 5.7% of surgeries. The main characteristics of each group are detailed in the table. Spine surgery is associated with postoperative complications in univariate analysis (p=0.048) with 2 reported spondylodiscitis but none were proven by a biopsy. In a multivariate logistic regression analysis, no predictive factors were identified. Conclusions: The occurrence of post-surgical complications in 6.7% of RA patients receiving RTX is similar with those reported with TNF alpha blockers (between 0 and 12.5%). No risk factor of complications was identified. Disclosure of Interest: None Declared